Adsorption of toxic dye using red seaweeds from synthetic aqueous solution and its application to industrial wastewater effluents - Al-Saeedi, Sameerah I.; Ashour, Mohamed; Alprol, Ahmed E. (Frontiers in Marine Science, 2023)
This study investigated the potential application of the dried powder from red seaweed Pterocladia capillacea as an eco-friendly adsorbent for the removal of Crystal Violet Dye (CV dye) from an aqueous solution (synthetic). During this study, the adsorption conditions for the adsorbent were calculated by changing different experimental parameters such as contact time, initial dye concentration, adsorbent dose, and pH of the solution. Different ini-tial concentrations of CV dye (5, 10, 20, 30, and 40 mg L–1), adsorbent doses (0.025, 0.05, 0.1, 0.2, and 0.3 g), temperature (25, 35, 45, and 55 °C), contact time (15, 30, 60, 120, and 180 min.), and pH (3, 5, 7, 9, and 11) were conducted in batch conditions. The adsorption mechanisms of CV dye onto the P. capillacea tissues were examined using various analytical techniques such as FTIR, BET, UV–Visible, and SEM. These characterizations suggest the average BET surface area of P. capillacea was 87.17 m2 g–1 and a pore volume of 0.10368 cc g−1. Moreover, according to the FT-IR study, the dye has been deposited inside the adsorbent’s pores after adsorption. The adsorption behavior of the adsorbent was investigated by performing both kinetic and equilibrium isothermal studies in batch conditions at 25 °C. Also, the thermodynamic factors showed the exothermic nature and physisorption of the adsorption process, which tends to be spontaneous at lower temperatures. In addition, Langmuir, Freundlich, Tempkin, and Dubinin-Radushkevich isotherm models were selected to evaluate the adsorption of CV dye on P. capillacea. The equilibrium adsorption data were best represented by the Freundlich, indicating multilayer adsorption on the heterogeneous surface. The qe experiment and calculation values for the pseudo-second-order and interparticle diffusion kinetic models were determined. The results showed that P. capillacea exhibited 98 % of CV dye removal from synthetic wastewater. Moreover, it will help to regenerate the adsorbents that can be used again to adsorb CV dye ions and develop a successful adsorption process. Finally, this study concluded that the dried powdered form of P. capillacea is an attractive source for the adsorption of CV dye from either a synthetic or aqueous solution.